Graphene based sensors in the detection of glucose in saliva – a promising emerging modality to diagnose diabetes mellitus. Issue 33 (5th August 2016) - Shanbhag, Vagish Kumar L.; Prasad, K. S.
Abstract : No more needles – a new modality to detect saliva glucose with graphene and its derivatives is on the horizon. Abstract : Saliva diagnostics is an emerging field in the branch of diagnostic medicine. Here in this focused mini-review, we address and discuss the emerging highly sensitive graphene and its derivative (graphene oxide and reduced graphene oxide) biosensors, which exhibit promising results in monitoring of glucose concentrations in saliva through a non-invasive way, thereby contributing to diagnosis, monitoring and formulation of a treatment plan for diabetes mellitus patients.